2010
DOI: 10.1021/jp101749h
|View full text |Cite
|
Sign up to set email alerts
|

Speciation in Aqueous MgSO4Fluids at High Pressures and High Temperatures from ab Initio Molecular Dynamics and Raman Spectroscopy

Abstract: Ab initio molecular dynamics simulations and in situ Raman spectroscopy are used to study the speciation in two molal aqueous MgSO 4 solutions at high pressures, P, and temperatures, T. While at ambient conditions the fluid is dominated by dissociated SO 4 2-(aq) ions and solvent-separated ion pairs, ion association strongly increases with increasing temperature and pressure along a 1.33 g/cm 3 isochore. At T ) 450 °C and P ) 1.4 GPa, the ν 1 (SO 4 2-) Raman band is well described by three Gaussian + Lorentzia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…1015 and 1028 cm -1 . It has been reported that the v1(SO4 2-) band becomes broader and the wavenumber increases with the increase of the length of inner-sphere ion pairs in aqueous MgSO4 solution [21,23,[35][36]. Considering the obvious higher-wavenumber shift of the v1(SO4 2-) band (Fig.…”
Section: Ion Association Between Uo2 2+ and So4 2-mentioning
confidence: 89%
See 3 more Smart Citations
“…1015 and 1028 cm -1 . It has been reported that the v1(SO4 2-) band becomes broader and the wavenumber increases with the increase of the length of inner-sphere ion pairs in aqueous MgSO4 solution [21,23,[35][36]. Considering the obvious higher-wavenumber shift of the v1(SO4 2-) band (Fig.…”
Section: Ion Association Between Uo2 2+ and So4 2-mentioning
confidence: 89%
“…980 cm -1 [34]. Both v1(UO2 2+ ) and v1(SO4 2-) bands can serve as indictors to investigate the complexation in the UO2SO4-H2O system because these two Raman bands are sensitive to changes in coordination environment [13][14][17][18][19][20][21][22][23].…”
Section: Ion Association Between Uo2 2+ and So4 2-mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, much study has gone into MgSO 4 , BaSO 4 , various lithium sulfates, and sulfate salts (Lemos et al 1991;Sakuntala andArora 1999, 2000;Chen et al 2009Chen et al , 2010Brand et al 2010;Machon et al 2010;Crichton et al 2011;Jahn and Schmidt 2010;Zhang and Sekine 2007;Santamaría-Pérez et al 2011;Antao 2012). Hydrated sulfates like gypsum undergo several structural changes below 10 GPa, while others like BaSO 4 exhibit few signs of transformation up to 20 GPa.…”
Section: Introductionmentioning
confidence: 99%